Evaluation of sports-specific mindful program (SSMP) for elite archers - Lo, K. K.; Tse, M. Y.; Chung, W. Y.; Law, P. S.; Sun, F. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction Mindfulness is trainable with a structured program and regular practice for better self-awareness, attentional control, and emotional regulation to improve athletic coping skills under stressful sports competitions [1]. The application of Mindfulness-Based Intervention (MBI) to elite sports performance has recently become very popular in precision sports and has a positive effect on shooting and dart throwing but no consistent findings in archery. This study aimed to evaluate the effectiveness of a newly developed Sports-Specific Mindful Program (SSMP) with eleven mindfulness-based intervention sessions and one sports-specific simulated competition session to enhance archers shooting performance, mindfulness levels, and flow states with decreasing anxiety levels.